Mathematical model of advanced refining technology adapted to the feedstock conditions of the republic of Kazakhstan; Petroleum and Coal; Vol. 58, iss. 7 - Nazarova G. Yu. Galina Yurievna; Ivashkina E. N. Elena Nikolaevna; Ivanchina E. D. Emilia Dmitrievna; Burumbaeva G. R. Galiya Rashidovna; Svarovsky A. Y. Aleksandr Yakovlevich; Seytenova G. Zh. (2016, 2016)
Title screen